Trust and team identification at multicultural workplaces : perceptions of Finnish HR professionals - Parttimaa, Eini (2017)
Growing global mobility has rapidly diversified workplace demographics across the world. Finland that has traditionally been considered a relatively uniform nation in terms of cultural and ethnic diversity has also experienced a shift in its population in recent decades. Despite the growing multiculturalism, established diversity management practices are yet to be developed in many Finnish organizations, and the subject has not gained much academic attention either. Still, competent intercultural leaders are often vital for both successful business results and for the well-being of their multicultural teams. The aim of this thesis is to shed light on the current state of international human resources management at Finnish workplaces. Through generic qualitative approach and semi-structured interviews this study reports how 5 Finnish HR professionals from different sized organizations perceive and promote social cohesion in the form of interpersonal trust and team identification in multicultural work groups. A narrative analysis of the collected data reveals that diversity management is not yet a well-established concept particularly at strongly results-driven workplaces with high power distance between the employees and the management. However, organizations where intercultural interaction is a considered more of an innate characteristic of every-day operations are more conscious of the value of a functional and attentive diversity management. The findings give an introduction to Finnish diversity management practices and could provide interesting point of views for example for small or start-up companies who do not have prior experience in managing a multicultural staff base. Still, further research is needed to study larges samples in order to produce generalizable data.